The Role of Logistic Services in the Suez Canal Ports for Supporting the Foreign Trade in Egypt - Mahmoud, Sally Mohamed Farid (Remah Review for Research and Studies, 2020)
The study aims to determine the role of logistic services in the Suez Canal ports for supporting the foreign trade in Egypt, and measuring the impact of logistic services in Egypt on foreign trade using an econometric model, to analyze efficiency of logistic services in the Suez Canal ports, includes East Port Said Port, West Port Said Port, Arish Port, Sokhna Port, and Adabiya Port. The results showed that the variables of logistic services (transport services, costs of export, the time required for export, and the movement of transport of containers) have a significant effect on Egypt's total foreign trade during the period (2004 - 2018). The logistics services have a major role in Egypt for promoting the foreign trade by facilitating the movement of ships, which reduce the cost of transporting goods and reduce the export time, this leads to increase the global competitiveness of Egypt.